... n − E o x i d a c i o ´ n {\displaystyle E_{\rm {celda}}=E_{\rm {reducci{\acute {o}}n}}-E_{\rm {oxidaci{\acute {o}}n}}} Aunque ... n F E c e l d a {\displaystyle \Delta G=-nFE_{\rm {celda}}} Ejemplo: 2 Ag + + Cu ( s ) ⟶ 2 Ag ( s ) + Cu 2 + {\displaystyle {\ ...
Ecuación sin balancear: K M n O 4 + N a 2 S O 3 + H 2 O → M n O 2 + N a 2 S O 4 + K O H {\displaystyle KMnO_{4}+Na_{2}SO_{3}+H ... 2 K M n O 4 + 3 N a 2 S O 3 + H 2 O → 2 M n O 2 + 3 N a 2 S O 4 + 2 K O H {\displaystyle 2KMnO_{4}+3Na_{2}SO_{3}+H_{2}O\to 2MnO ... 2 M n ( a q ) 2 + + 5 N a B i O 3 ( s ) → 7 H 2 O + 2 M n O 4 ( a q ) − + 5 B i ( a q ) 3 + + 5 N a ( a q ) + {\displaystyle ... 8 H 2 O + 2 M n ( a q ) 2 + → 2 M n O 4 ( a q ) − + 16 H ( a q ) + + 10 e − 10 e − + 30 H + + 5 B i O 3 ( s ) − → 5 B i ( a q ...